الضغوط المهنية و علاقتها بصحة النفسية لدى ممرضات بمستشفى العقيد لطفي 240 سرير بالأغواط - نور الهدى ريان; عفاف بومقواس; بلمقدم فاطمة (My University, 2023)
The current study aimed to investigate occuptionql stresses and their relqtionship to mental health among public health nurses at colonel lotfi hospital 240 beds, where the descriptive correlational approach was relied upon by distributing [30] questionnaires to the study sample divided into two questionnaires. Aquestionnaire about mental health divid into four dimension: Obsessive- compulsive factor, depression factor,anxiety factor and enemy factor. After statistical treatment of the data, we reached the following results: -Existence of a relationship between occupational stress and mental health – existence of a high level occupational stress and the presence of – low level of mental health there no differences in occupational stress according to the variable of social status and seniority. Keywords: occupational stress mental health